RANCANG BANGUN SISTEM INFORMASI INDUSTRI KELAPA DI PROVINSI SULAWESI UTARA BERBASIS WEB-GIS - Grentino Marcelo Durand; Dedie Tooy; Sandra E. Pakasi (COCOS, 2019)
ABSTRACT The purpose of this research is to design and build an information system of coconut industry in North Sulawesi province by utilizing web-based Geographic Information System (GIS) and internet technology. This research was conducted to provide information of coconut industry in the web-GIS based North Sulawesi province with a wide range. This research uses the SDLC (System Development Life Cycle) method or is known as a system development lifecycle. Information system on the coconut industry in North Sulawesi province can be accessed by internet users by typing the URL in the Addressbar http://industrikelapasulut.unaux.com/. Keywords : Coconut industry. Information systems, WEB-GIS